Artificial Intelligence and Fact Checking in Africa: Between Logic of Dependency and the Limits of Automation - Seck Sarr, Sokhna Fatou (European Scientific Journal, ESJ, 2024)
This article focuses on fact-checking initiatives in the context of the rise of artificial intelligence. With reference to theories of the political economy of communication and platform studies, this study sheds light on the very confusing evolution of initiatives in Africa. The approach combines content analysis and distanced observation of two fact-checking platforms, chosen on the basis of their local roots and the experimentation of smart tools: Africa Check and Check4Decision. The results highlight the economic and technological dependencies of African platforms on GAFAM via fact-checking services and an automation process that is far from complete with regard to local realities. It appears that the African context provides a different perspective with structural constraints and "cultural" algorithmic biases.